Aquatic Plants Native to Europe - Lambrechts, Isa A.; Gibango, Lydia; Chrysargyris, Antonios; Tzortzakis, Nikos G.; Lall, Namrita (My University, 2020)
Europe consists of three ecological zones, namely subtropical (Portugal, Spain, Italy, and Greece), boreal (Iceland, Norway, Sweden, and Finland), and temperate (the United Kingdom and the majority of Europe). The temperate zones are home to aquatic species such as Nasturtium officinale and Ceratophyllum demersum. The subtropical zones are home to the aquatic species such as Vallisneria spiralis. The descriptions of several aquatic species native to Europe, including common names, botanical characteristics, distribution map, traditional uses, bioactivity, and compounds isolated, are discussed in this chapter.